Effect of neodymium:YAG laser capsulotomy on visual function in patients with posterior capsule opacification and good visual acuity. Issue 3 (March 2016) - Yotsukura, Erisa; Torii, Hidemasa; Saiki, Megumi; Negishi, Kazuno; Tsubota, Kazuo
Abstract : Purpose : To evaluate the effect of neodymium:YAG (Nd:YAG) laser capsulotomy on the visual function in patients with posterior capsule opacification (PCO) and good visual acuity. Setting : Keio University Hospital, Tokyo, Japan. Design : Observational case series. Methods : Eyes were evaluated that had previous cataract surgery with a clinical diagnosis of PCO requiring Nd:YAG laser capsulotomy regardless of a good corrected distance visual acuity (CDVA) (at least 20/20). The CDVA, 10% low contrast visual acuity (LCVA), wavefront aberrations from the 3rd to 6th order, and retinal straylight were measured before and after Nd:YAG laser capsulotomy. Results : The study included 16 eyes of 16 patients (10 men, 6 women; mean age 69.5 years ± 9.3 [SD]). The mean CDVA, LCVA, and straylight after Nd:YAG laser capsulotomy improved significantly ( P < .05). The root mean square (RMS) of the 3rd Zernike coefficients (S3) and the RMS of the total higher‐order aberrations (HOAs) from the 3rd to 6th order decreased significantly after capsulotomy ( P < .05). The straylight correlated significantly with the total HOAs ( r = 0.727, P = .002) and S3 ( r = 0.748, P = .001) before capsulotomy. Subjective symptoms resolved after capsulotomy in all cases. Conclusions : Neodymium:YAG laser capsulotomy enabled a significant improvement in visual function even in patients with PCO with good visual acuity. Straylight measurements might be useful to determine the indications for Nd:YAG laser capsulotomy when patients report visual disturbances without decreased visual acuity. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.